PENGARUH METODE EKSPERIMEN TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS III SDN 19 SITIUNG - Ayu Ningsih Almirus; Tiya Nurni Khairita; Lisda Dewi Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes in Natural and Social Sciences (IPAS) among third-grade students at SDN 19 Sitiung indicate the need for a learning method that provides direct learning experiences. This study aimed to determine the effect of the experimental method on students’ IPAS learning outcomes. A quantitative approach was employed using a pre-experimental design in the form of a one-group pretest-posttest design. The sample consisted of 31 third-grade students selected through saturated sampling. The research instrument was a multiple-choice learning outcome test administered before and after the treatment. Data were analyzed using descriptive statistics and a paired sample t-test with IBM SPSS Statistics 25. The results showed that the mean pretest score of 61.94 increased to 78.32 in the posttest, with a mean difference of 16.39 points. The paired sample t-test result indicated t(30) = 14.08 and p < 0.001, showing a significant difference between students’ learning outcomes before and after the implementation of the experimental method. These findings suggest that the experimental method positively affects IPAS learning outcomes by enabling students to observe, conduct trials, verify concepts, and draw conclusions directly. Therefore, the experimental method can be considered an effective alternative learning method for improving IPAS learning outcomes in elementary schools.